Identifikasi Bahaya dan Risiko K3 Pada UMKM Pembuatan Tahu UG Priangan di Bojongsari Tahun 2023 - Getar Millennium Udara; Rini Handayani; Putri Handayani; Ahmad Irfandi (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
There are several strategies available to manage risk, including shifting responsibility to others, avoiding potential hazards, reducing the severity of negative outcomes, or choosing to accept and deal with the consequences to some or all extent. As the first step in implementing OHS. This research aims to identify OHS hazards and risks in UG Priangan tofu-making MSMEs in Bojongsari 2023. The type of research is semi-quantitative with primary data collection through in-depth interviews with 3 informants and observation. The data that has been obtained is processed and analyzed descriptively. The results of hazard identification found 6 types of hazards, namely mechanical hazards from slippery floors, electrical hazards from machine use, physical hazards from noise from the sound of steam pressure, chemical hazards from soybean water and seed water (vinegar acid), ergonomic hazards from repetitive movements, and psychosocial hazards from working hours. The risks found were 10 risks of work accidents and 15 risks of occupational diseases. It is recommended for business owners to provide information about the risks of work processes, tools, and materials in the workplace and conduct OHS risk assessments.